Cytotoxic Lesion in the Splenium of Corpus Callosum Secondary to Subacute Methotrexate Neurotoxicity - Al-Awwad, Ahmad A.; Koriesh, Ahmed (Avicenna Journal of Medicine, 2021)
Methotrexate neurotoxicity can present with a wide spectrum of neurologic symptoms and brain magnetic resonance imaging (MRI) typically demonstrates cerebral edema, demyelination, multifocal white matter necrosis, and atrophy relatively selective for the deep cerebral white matter. Here, we report a case of subacute methotrexate neurotoxicity in a 40-year-old man with B cell acute lymphoblastic leukemia. Brain MRI showed cytotoxic lesion in the splenium of corpus callosum and left middle cerebellar peduncle. Patient significantly improved 24 hours after receiving oral dextromethorphan. Methotrexate neurotoxicity should be suspected in any symptomatic patient receiving high dose of methotrexate or intrathecal methotrexate therapy. Dextromethorphan should be considered in these patients as it can modulate the excitatory responses to homocysteine and its metabolite which are usually elevated in such patients.
Keywords: methotrexate neurotoxicity; splenium lesion; dextromethorphan